Architecture of collapse: regime shift and recovery in an hierarchically structured marine ecosystem. (11th October 2016) - Daskalov, Georgi M.; Boicenco, Laura; Grishin, Alexandre N.; Lazar, Luminita; Mihneva, Vesselina; Shlyakhov, Vladislav A.; Zengin, Mustafa
Abstract: By the late 20th century, a series of events or 'natural experiments', for example the depletion of apex predators, extreme eutrophication and blooms of invasive species, had suggested that the Black Sea could be considered as a large ecosystem 'laboratory'. The events resulted in regime shifts cascading through all trophic levels, disturbing ecosystem functioning and damaging the water environment. Causal pathways by which the external (hydroclimate, overfishing) and internal (food web interactions) drivers provoke regime shifts are investigated. Statistical data analyses supported by an interpretative framework based on hierarchical ecosystem theory revealed mechanisms of hierarchical incorporation of environmental factors into the ecosystem. Evidence links Atlantic teleconnections to Black Sea hydroclimate, which together with fishing shapes variability in fish stocks. The hydroclimatic signal is conveyed through the food web via changes in productivity at all levels, to planktivorous fish. Fluctuating fish abundance is believed to induce a lagged change in competitor jelly plankton that cascades down to phytoplankton and influences water quality. Deprived of the stabilising role of apex predators, the Black Sea's hierarchical ecosystem organisation is susceptible to both environmental and anthropogenic stresses, and increased fishing makes fish stock collapses highly probable. When declining stocks are confronted with burgeoning fishing effort associated with the inability of fishery managers and decision‐makers to adapt rapidly to changes in fish abundance, there is overfishing and stock collapse. Management procedures are ineffective at handling complex phenomena such as ecosystem regime shifts because of the shortage of suitable explanatory models. The proposed concepts and models reported here relate the hydroclimate, overfishing and invasive species to shifts in ecosystem functioning and water quality, unravelling issues such as the causality of ecosystem interactions and mechanisms and offering potential for finding ways to reverse regime shifts. We advocate a management approach aiming at restoring ecosystem hierarchy that might mitigate the costly consequences of regime shifts.